Clay Filled Aluminum Product - Mohd Ichwan, Nasution, Ir.; Shamsul Baharin, Jamaludin, Assoc. Prof. Dr.; Che Mohd Ruzaidi, Ghazali, Assoc. Prof.; Faizul, Che Pa; Chek Idrus, Omar (Malaysian Invention and Design Society (MINDS), 2010)
Ir. Mohd Ichwan Nasution and his team won gold for Clay Filled Aluminum Product. ITEX 2007, 18th - 20th May 2007 was held at Kuala Lumpur Convention Centre (KLCC), Kuala Lumpur.